Pengolahan Salep Madu Hitam Hutan Jambi untuk Perawatan Luka - Merdekawati, Diah; Astuti, Ani; Hartesi, Barmi (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2019)
SS. M.J Local Black Honey home production. In Pijoan Jaluko Village, Muaro Jambi Municipality is one of the black honey producers that is potentially developed to be more comparative and competitive. The development of prospective processed honey product is as health product in the form of ointment that is highly needed by people, considering that such product is not in the market yet. The development of processed honey product into health ointment by SS. M.J Local Black Honey home production has several limitations namely lacking knowledge and skill on processing, business capital, and marketing. Thus, efforts for empowerment are needed with step by step methods namely socialization, training, practice, and market meet. The success of this empowering activity is shown from the capability of SS. MJ. Local Black Honey home production to produce processed product in the form of Forest Honey Ointment, the knowledge of business capital development method, and the ability to market the product after getting license from BPOM.